New Technique for Preconditioning of the Spinal Cord Before Endovascular Repair of Descending Thoracic and Thoracoabdominal Aortic Aneurysms. (October 2019) - Sonesson, Björn; Dias, Nuno V.; Resch, Timothy A.
Purpose: To propose a new simplified technique to occlude multiple segmental arteries for staging and preconditioning of the spinal cord to decrease the potential for spinal cord ischemia after thoracic and thoracoabdominal aortic aneurysm repair.Technique: A thoracic stent-graft that flares out to a maximum of 51 mm is deployed in a standard fashion covering all segmental arteries where graft-wall apposition occurs in the first ~20 cm of the aneurysm. The segmental arteries are always closed at their ostia in contrast to selective coil embolization, where there is a risk of more peripheral closure. Follow-up imaging shows thrombus lining the stent-graft–covered portion of the aneurysm and secondary proximal segmental artery occlusion.Conclusion: A new and fast way of staging and preconditioning the spinal cord using a modified stent-graft prior to definitive repair might be an alternative to segmental artery embolization.